Successful control of a large outbreak of HIV infection associated with injection of cathinone derivatives in Tel Aviv, Israel. (May 2017) - Katchman, E.; Ben-Ami, R.; Savyon, M.; Chemtob, D.; Avidor, B.; Wasserman, A.; Zeldis, I.; Girshengorn, S.; Amitai, Z.; Sheffer, R.; Turner, D.
Abstract: Objectives: Outbreaks of HIV infection have been linked to injectable drug abuse, but specific triggers often remain obscure. We report on an outbreak of primary HIV infection among people who inject drugs (PWID) in Tel Aviv, associated with a local shift in drug-use practices. Methods: A cluster of primary HIV infection cases in PWID was detected in May 2012. Retrospective and prospective multi-hospital case finding was initiated. PWID were interviewed and risk factors for primary HIV infection were identified. Starting in December 2012, a multifaceted intervention was implemented, including educational activities, increasing syringe exchange supplies, active screening, early initiation of antiretroviral therapy, and referral to drug withdrawal programmes. Results: Forty-two PWID with primary HIV infection were detected between May 2012 and April 2013. Compared with the corresponding pre-outbreak period, the annual incidence of primary HIV infection in PWID increased from 0 to 20 cases/1000 population (p <0.0001). Sixty-nine per cent were hospitalized because of concomitant bacterial infections and sepsis. Phylogenetic analysis of HIV isolates from case patients showed tight clustering suggesting a single common source of infection. The outbreak was temporally related to a widespread shift from heroin to injectable cathinone-derivatives and buprenorphine, which entailed high-risk injection practices. Targeted intervention resulted in a dramatic and sustained reduction in HIV infection in the PWID population. Conclusions: Injectable amphetamines are gaining momentum among PWID worldwide. Tracing of this outbreak to cathinone use and implementing a targeted intervention programme effectively terminated the outbreak.